«Introduction» - Freire, A. (Political Representation and Citizenship in Portugal: from Crisis to Renewal?, 2020)
Marco Lisi, André Freire & Emmanouil Tsatsanis (2020), «Introduction», Marco Lisi, André Freire & Emmanouil Tsatsanis (editors) (2020), Political Representation and Citizenship in Portugal: from Crisis to Renewal?, Lexington Books – Rowman & Littlefield, 2020.